Clinical researchRed cell alloimmunization and autoantibodies in Egyptian transfusion-dependent thalassaemia patients - Ahmed, Azza Mohamed; Hasan, Nehal Salah; Hassan Ragab, Shadia; Habib, Sonia Adolf; Emara, Nahed Abdelmonem; Ahmed Aly, Azza (Archives of Medical Science, 2010)
Introduction: The objective of this study was to explore the frequency of red cell alloantibodies and autoantibodies among -thalassaemia patients who received regular transfusions. Material and methods: This study included 501 patients with -thalassaemia. This work planned to study the presence of alloantibodies and autoantibodies to different red cell antigens in multitransfused thalassaemia patients using the ID. Card micro typing system. Results: Of a total of 501 -thalassaemia patients included in the study, 11.3% of patients developed alloantibodies; 9.7% of these alloantibodies were clinically significant. The most common alloantibodies were anti-K, anti-E and anti-C. The rate of incidence of these alloantibodies was 3.9%, 3.3% and 1.7% respectively. Autoantibodies occurred in 28.8% of the patients and 22.1% of these antibodies were typed IgG. There was a significant association between splenectomy with alloimmunization and autoantibody formation (p = 0.03, p = 0.001 respectively). There was no significant association between alloantibody, autoantibody formation and number of transfused packed red cells. Conclusions: Alloimmunization to minor erythrocyte antigens and erythrocyte autoantibodies of variable clinical significance are frequent findings in transfused -thalassaemia patients. There is an association between absence of the spleen and the presence of alloimmunization and autoantibody formation.